Effect of streptozotocin-induced diabetes on GLUT-4 phosphorylation in rat adipocytes. - Begum, N (1992)
We have examined the regulation of GLUT-4 phosphorylation in adipocytes isolated from diabetic rats. Despite progressive (40-70%) reductions in GLUT-4 protein contents on the 2nd, 7th, and 14th day of diabetes, the phosphorylation of GLUT-4 was increased two- to fourfold. These alterations were accompanied by concomitant reductions (40-66%) in the insulin-stimulated 2-deoxyglucose transport. Insulin treatment of diabetic animals for 5 d restored glucose transport activity, GLUT-4 protein, and GLUT-4 phosphorylation to control levels whereas vanadate and phlorizin were ineffective. In control adipocytes, insulin promoted GLUT-4 translocation from the low density microsomal (LDM) pool to the plasma membranes (PM) and decreased the state of GLUT-4 phosphorylation. In adipocytes isolated from the diabetic rats, insulin failed to stimulate GLUT-4 translocation and to decrease GLUT-4 phosphorylation. To explore the mechanism of the diabetes-induced increases in the GLUT-4 phosphorylation, we investigated phosphoserine phosphatase (PSPase) activities using 32P-labeled GLUT-4 and phosphorylase "a" as substrates. Diabetes resulted in 50-60% increase in the particulate PSPase activity and concomitant reductions in cytosolic PSPase activities. Although reduced cytosolic PSPase activity correlated with an inadequate dephosphorylation of LDM GLUT-4, the existence of highly phosphorylated PM GLUT-4 in the presence of increased particulate PSPase activity required additional explanation. To address this problem, we used PM GLUT-4 from diabetic rats as a substrate of particulate PSPase. Highly active diabetic particulate PSPase, which dephosphorylated control GLUT-4 and phosphorylase a, failed to dephosphorylate PM GLUT-4 from diabetic rats. These data suggest that PM GLUT-4 from diabetic rats is unable to interact with PSPase or that its phosphorylation sites are not accessible to PSPase action. In summary, an induction of diabetes with streptozotocin resulted in significant increases in GLUT-4 phosphorylation. In contrast to normal cells, insulin failed to promote GLUT-4 recruitment to the plasma membranes and its dephosphorylation in diabetic adipocytes. At the same time, diabetes appears to induce redistribution of PSPases, resulting in lower cytosolic activity and higher particulate activity. It also appears that the existence of highly phosphorylated GLUT-4 in the plasma membranes of diabetic adipocytes resulted from its inability to interact with particulate PSPases.